Editorial - Teye, Prof. G. A. (UDS International Journal of Development, 2021)
The first issue of volume 8 of the UDS International Journal of Development (UDSIJD) has been published. A total of eight papers are included in Volume 8, Issue 1 of the UDSIJD. Seven papers cover Humanities whilst one in the Agricultural Sciences. The UDSIJD has fully migrated its operations to an online journal management system and therefore, all authors, contributors, reviewers, and editors are to interact via the journal system. By this, it is imperative that one visits his/her dashboard regularly, to track updates to manuscripts and review. The UDSIJD urges all authors and contributors to pay particular attention to the journal’s guidelines and adhere strictly to them. Also, comments from peer review are meant to improve the quality of the manuscripts and hence should not be personalized. We encourage young academics, researchers, development practitioners, and entrepreneurs to submit original research across disciplines for consideration to be published in our journal. The UDSIJD strives to enhance scholarly communications with a development focus, on a regular and sustained basis. The Editorial Team wishes to sincerely thank the University Management, authors, reviewers, and staff of the Journal and all those who in diverse ways have supported in making this issue of the journal a reality. The Editor-in-Chief Prof. G. A. Teye